Pura Agung Mpu Kuturan: Textual Review and Its Implications in the Formation of Academic Character Based on Ethnopedagogy - Ardiyasa , I Nyoman Suka; Kurniawan, Made Ferry; Anggraini, Putu Maria Ratih (Universitas Pendidikan Ganesha, 2024)
One of the efforts to construct local values ​​as a basis for instilling ethno-pedagogical characters is to interpret the character of Mpu Kuturan which is manifested through the construction of the Pura Agung Mpu Kuturan at the Sekolah Tinggi Agama Hindu Mpu Kuturan Singaraja, Bali. This research emphasizes philological studies. The researcher reads various manuscripts about the remains of Mpu Kuturan's knowledge as a cultural heritage in Bali. The context is important to examine because it is useful for providing a textual description, especially the reconstruction of local values ​​to be used as a reference for pedagogical values. The stages of the Pura Agung Mpu Kuturan ceremony contain academic values ​​based on ethnopedagogy. First, Melasti Segara and Mapekelem-Mapapada Wewalungan Tawur, meaning the construction of eco-pedagogical values ​​and critical learning media, because they are the personification of the universe. Second, Nyenuk, Ngamargiang Kekundang, Ngaturang Guru lan Bendu Piduka/Ngrsi Bojana, meaning the construction-systematization of the thinking process. The symbolization of colors and the placement of gods in various directions symbolically signify the thinking ability of a learner or academic must be adjusted to the situation and conditions or social gradation of each diverse society. Third, Nangun Ayu-Makebat Daun, as a constructive symbol of metacognitive thinking - open. Makebat daun means opening up a new life or hope. If interpreted, the procession of the ceremonies above is the result of human creativity (as homo-esparan) to visualize or personify the form and presence of God which is abstract in nature into a concrete form.